Faecal haemoglobin and faecal calprotectin as indicators of bowel disease in patients presenting to primary care with bowel symptoms. Issue 9 (20th August 2015) - Mowat, Craig; Digby, Jayne; Strachan, Judith A; Wilson, Robyn; Carey, Francis A; Fraser, Callum G; Steele, Robert J C
Abstract : Objective: In primary care, assessing which patients with bowel symptoms harbour significant disease (cancer, higher-risk adenoma or IBD) is difficult. We studied the diagnostic accuracies of faecal haemoglobin (FHb) and faecal calprotectin (FC) in a cohort of symptomatic patients. Design: From October 2013 to March 2014, general practitioners were prompted to request FHb and FC when referring patients with bowel symptoms to secondary care. Faecal samples were analysed for haemoglobin (EIKEN OC-Sensor io) and calprotectin (BÜHLMANN Calprotectin ELISA). Patients triaged to endoscopy were investigated within 6 weeks. All clinicians and endoscopists were blind to the faecal test results. The diagnostic accuracies of FHb and FC for identification of significant bowel disease were assessed. Results: 1043 patients returned samples. FHb was detectable in 57.6% (median 0.4 µg/g, 95% CI 0.4 to 0.8; range 0–200). FC at 50 µg/g or above was present in 60.0%. 755 patients (54.6% women, median age 64 years (range 16–90, IQR 52–73)) returned samples and completed colonic investigations. 103 patients had significant bowel disease; the negative predictive values of FHb for colorectal cancer, higher-risk adenoma and IBD were 100%, 97.8% and 98.4%, respectively. Using cut-offs of detectable FHb and/or 200 µg/g FC detected two further cases of IBD, one higher-risk adenoma and no additional cancers. Conclusions: In primary care, undetectable FHb is a good 'rule-out' test for significant bowel disease and could guide who requires investigation.